4D dynamic simulation of coal oxidation heating law in gobs with heterogeneous porosity - ZHOU Pei-ling; ZHANG Ying-hua; HUANG Zhi-an; YUAN Fei; GAO Yu-kun; WANG Hui; SUN Qian (工程科学学报, 2016)
Using the Fluent dynamic mesh model to realize the 4D dynamic movement of a gob and inputting the kinetic mechanism of coal low-temperature oxidation and the dynamic change of heterogeneous porosity into Fluent through the user defined function,4D dynamic simulation is performed on the spontaneous heating law in a gob for U + L ventilation of a certain mine. The results show that unsteady heterogeneous porous media can be more realistic in response to the change of porosity,which exponentially decreases with time. The greater the advancing speed of the working face, the smaller the heating rate, and the average heating rate at an advancing speed of 3.6 m·d-1 is 1/5 of that at an advancing speed of 1.2 m·d-1. However, the higher the advancing speed, the deeper the depth of the high temperature region, which is unfavorable for the prevention from spontaneous combustion of coal. Because of the existence of a tail roadway in the gob, the temperature field expands, the temperature rises, the main way to release CO is the tail roadway, and the amount of CO from the tail roadway is 10 times that from the outlet. Finally, the results are verified by the field test data, indicating that the simulation results are correct and reliable.